Epic devotions : 52 weeks in the story that changed the world. - Armstrong, Aaron (Nashville, TN : B & H Kids, 2019)
Epic Devotions: 52 Weeks in the Story that Changed the World is a graphic-novel inspired weekly devotional based on Epic: The Story that Changed the World. Each insightful devotion circles back to the one big story of Jesus and makes biblical events more relevant for today's youth. The book features familiar yet reimagined art from the One Big Story brand that is perfect for engaging older kids and preteen readers.
Junior
Keywords: Bible. -- Juvenile literature -- Comic books, strips, etc; Bible; Bible; Bible; Bible stories -- Juvenile literature -- Comic books, strips, etc; Bible stories; Comics (Graphic works); Comics (Graphic works); Literature